The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1678-457x.20516
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of functional properties of eight walnut (Juglans regia L.) genotypes

Abstract: Eight walnut (Juglans regia L.) genotypes were assessed for the glutathione (GSH) and total phenolic contents (TPC), as well as their antioxidant capacities. The GSH contents were between 1.1 and 7.2 mg 100 g -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
(45 reference statements)
0
13
0
1
Order By: Relevance
“…According to the authors cited, the average total polyphenol content in walnuts is about 1591.5 mg/100g. On the other hand, Cerit et al [32] reported a much higher total polyphenol content (TPC) value in nuts cultivated in Turkey. The authors stated that the content of polyphenols in walnuts ranged from 34.0 mg GAE/g to 50.3 mg GAE/g.…”
Section: Resultsmentioning
confidence: 99%
“…According to the authors cited, the average total polyphenol content in walnuts is about 1591.5 mg/100g. On the other hand, Cerit et al [32] reported a much higher total polyphenol content (TPC) value in nuts cultivated in Turkey. The authors stated that the content of polyphenols in walnuts ranged from 34.0 mg GAE/g to 50.3 mg GAE/g.…”
Section: Resultsmentioning
confidence: 99%
“…A mixture of methanol and water was also employed for the assessment of individual phenolic compounds, TPC, and antioxidant potential in kernels, oils, and bagasse pellets of different walnut cultivars [180]. Eight genotypes of Turkish walnuts were selected by Cerİt, et al [181] to assess their kernels from the viewpoint of glutathione and TPC, as well as their antioxidant capacities. In this work, the authors used methanol:water (70:30) solution for the preparation of extracts.…”
Section: The Solvents Used For the Preparation Of Walnut Extractsmentioning
confidence: 99%
“…In QSAR modeling, ANNs must be built with care, to avoid over‐fitting due to noise in the data. Several studies were published on the application of MLP ANNs for quantitative prediction of antioxidant activity …”
Section: Introductionmentioning
confidence: 99%
“…For instance, Cerit et al have used an MLP ANN for prediction of ferric ion reducing antioxidant power (FRAP) from phenolic content of red pepper and grape seeds. The authors report strong predictive ability with average errors of 8.5 and 10.1% for training and validation sets of samples, respectively.…”
Section: Introductionmentioning
confidence: 99%